en - Sumarta, I Wayan Ardi (e-Journal of Linguistics, 2022)
The existence of outdoor signs in places of worship not only conveys information, but also has the intention of persuasive invitations or appeals and contains symbolic meanings. This study aims to analyze the outdoor signs that exist in the mosque environment around Denpasar. The source of the data for this research is outdoor signs in mosques around Denpasar. This study uses methods and techniques which are divided into three stages, namely (1) The method of data collection using the method of documentation and observation. Data collection techniques with observation and photography techniques. (2) Data analysis using qualitative methods. The data analysis technique used descriptive analytic technique by describing the facts which were then followed by data analysis; (3) Presentation of the results of data analysis using informal methods and formal methods with the help of deductive techniques. The results show that outdoor signs are not only information elements such as announcements or notifications, but also have persuasive power and meaning.